STUDI HADIS TEMATIK - Maulana Ira (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2018)
This article discuss about thematic study of hadith (mawḍū'ī) methodologically.Mawḍū'ī method is collect hadith related to the topic or purpose.Thematic approach can be understood through content and purpose ofa hadith by studying relatedto it and see each correlation in order to obtain a full understanding on it. There are some steps in studying hadith thematic. study starts from the determination of themes or issues which will be discussed, collecting hadith related to the theme, categorization hadith, i'tibār whole sanad hadith, sanad research related to their personality and intellectual capacity of the narrators, study on matan related to proof whether 'illat (disability) and syāż (irregularities), an assessment of the themes that contain a similar meaning, comparison commentary tradition, completing discussions with the hadith or verse support, preparation of research results, and to be closed with a conclusion